Posterior shoulder instability due to isolated reverse HAGL lesion in a young gymnast: A rare mechanism of injury and surgical technique. (August 2020) - Maalouly, Joseph; Aouad, Dany; Ayoubi, Rami; Dib, Nabil; El Rassi, Georges
Abstract: Humeral avulsion of the inferior glenohumeral ligament (HAGL) is a relatively important cause of shoulder instability, becoming a field of interest in the literature. Reverse HAGL lesions, a rare pathology compared to anterior disruptions; have been documented in only few cases as a notable cause of posterior instability. We describe in detail the mechanism of injury, diagnosis, arthroscopic repair and results.